The art of integrative counseling - Corey, Gerald; Haynes, Robert; Walters, Thomas (Australia : Brooks/Cole, 2001)
This video let you see an integrative approach in action. As you observe Dr. Gerald Corey using various theoretical models and techniques with a single client (Ruth), you can visualize the advantage of developing a personal, integrated counseling style
Writer, Thomas Walters
Keywords: Counseling; Psychotherapy